Implementasi Rehabilitasi Jantung Fase Satu terhadap Fisik dan Psikologis Pasien Sindrom Koroner Akut (SKA) - Muhammad Iqbal; Yanny Trisyani; Aan Nur’aeni (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of phase one cardiac rehabilitation on the physical and psychological aspects of ACS patients. The method used is scoping review by searching for articles in several databases, namely PubMed, CINAHL, ScienceDirect and Google Scholar. The results showed that phase one cardiac rehabilitation positively affects the physical and psychological aspects of patients, especially in improving hemodynamic function, reducing levels of anxiety and depression and increasing the quality of life of ACS patients. In conclusion, cardiac rehabilitation is proven to increase functional capacity and reduce levels of anxiety and depression, which leads to a reduced risk of poor quality of life in patients with the acute coronary syndrome. Keywords: Depression, Anxiety, Quality of Life, Phase One Cardiac Rehabilitation, Acute Coronary Syndrome